Quand Patrimoine et haute-technologie se rencontrent… - Bernard Tilkens (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art, 2008)
New Optical technologies are more and more often used in methods of conservation and restoration of works of art. Investigation, broadcasting and accessibility to Cultural Heritage have now new systems to complete their missions. The following examples will try to illustrate potentialities of the devices developed by Deios. They are coming from real applications.